Juridical Construction Of Building Rights Over Management Rights In The Land Law System - Anjas Setiawan; Helmi Helmi; Rosmidah Rosmidah (JURNAL AKTA, 2026)
In the practice of national land administration, the legal instrument known as Land Management Rights (HPL) has emerged as a representation of the State's Sovereign Rights over land. However, their place in the land rights system is still up for discussion, particularly when Building Use Rights (HGB), which are widely utilized in the construction of industrial, residential, and commercial zones, are granted on top of them. Because it deals with legal certainty and protection for the interests of rights holders and investors, this matter is important. The goal of this study is to determine where HPL stands in relation to the land law system and establish the legal connection between HPL holders and HGB holders. Through the examination of primary, secondary, and tertiary legal sources, the approach utilized is normative juridical legal research with a legislative and conceptual perspective. The discussion's findings indicate that although it is situated inside an HPL management area, HGB continues to be a land right given by the government, but HPL is an administrative authority originating from the State's Right of Control rather than a property right as described by the Basic Agrarian Law. As a result, the connection between HPL and HGB holders is administrative-contractual in character, but the source of authority for issuing HGB is not altered. Therefore, a conceptual clarification is necessary to guarantee legal certainty.